The role of financial incentives – as SMB development factor - Ермекбаева, Б.; Тасбулатова, У. (Journal of Economic Research & Business Administration, 2017)
The paper considers the role of financial incentives for the development of entrepreneurship. It revealed the contribution of small and medium-sized businesses in the country’s economy. According to state programs in Kazakhstan, such as the Strategic Plan of Development of Kazakhstan till 2050, the State program for accelerated industrial-innovative development of Kazakhstan for 2015-2019, the development of small and medium-sized businesses identified as a priority. The experience of foreign countries such as the US, Japan and France, financial incentives for small and medium-sized businesses were Reviewed and analyzed. The negative factors for the development of small and medium business in Kazakhstan were identified . the state financial measures to stimulate entrepreneurship was presented, the most common form used by tax incentives, forms of state financial and credit support of small business were described, measures to improve the financial - banking system were proposed contributing to the development of small medium-sized businesses.